2021
DOI: 10.31234/osf.io/aqhmx
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Episodic memory processes modulate how schema knowledge is used in spatial memory decisions

Abstract: Schema knowledge can dramatically affect how we encode and retrieve memories. Current models propose that schema information is combined with episodic memory at retrieval to influence memory decisions, but it is not known how the strength or type of episodic memory (i.e., unconscious memory versus familiarity versus recollection) influences the extent to which schema information is incorporated into memory decisions. To address this question, we had participants search for target objects in semantically expect… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 55 publications
(82 reference statements)
2
3
0
Order By: Relevance
“…We then separately examined each episodic memory process and their interactions with schema congruency. We found that, in line with prior work (Ramey et al, 2021), recollection suppressed schema effects in the sample overall (Figure 2). That is, when scenes were recollected, there was no significant effect of schema congruency on target distance, t(4188) =1.845, p=.07, d=.057, such that schema information no longer influenced spatial accuracy.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…We then separately examined each episodic memory process and their interactions with schema congruency. We found that, in line with prior work (Ramey et al, 2021), recollection suppressed schema effects in the sample overall (Figure 2). That is, when scenes were recollected, there was no significant effect of schema congruency on target distance, t(4188) =1.845, p=.07, d=.057, such that schema information no longer influenced spatial accuracy.…”
Section: Resultssupporting
confidence: 88%
“…To probe effects of familiarity strength, we examined the linear gradient of familiarity responses from "sure new" to "sure old." As in prior work (Ramey et al, 2021), the effects of schema congruency on spatial accuracy were reduced by familiarity such that as familiarity strength increased, schema congruency effects decreased, β=-.16, t(7000)=-7.84, p<.0001. AUT score was not significantly related to differences in how familiarity strength influenced spatial accuracy overall, β=.01, t(4588)=.87, p=.39, nor in how familiarity strength interacted with schema congruency effects, β=.01, t(6951)=.73, p=47.…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations